KARAKTER SPASIAL DAN TEMPORAL CURAH HUJAN BULANAN KABUPATEN JEMBER BERDASARKAN DATA CHIRPS - Purnamasari, Ika; Abdillah, Moc. Reza Wahyu; Wijayanto, Yagus; Saputra, Tri Wahyu; Ristiyana, Suci; Budiman, Subhan Arif (Jurnal Tanah dan Sumberdaya Lahan, 2024)
Jember Regency is one of the national food storage areas. One of the most important resources in cultivating food crops is water which comes from rainfall. The existence of rainfall data is very important in planning and implementing agricultural activities. Limited rainfall data is the main problem for agricultural planning. One solution to this problem is to utilize rainfall data from CHIRPS (Climate Hazards Group Infrared Precipitation Station). The use of CHIRPS data is still biased data, so bias correction is needed to measure the level of accuracy of CHIRPS data for estimating rainfall in an area. Bias correction is carried out using two methods, namely multiple linear regression and power regression. The correction results show that the multiple linear regression method is able to produce monthly rainfall that is close to observations with an RMSE value of 3.9 and a coefficient of determination of 0.99. Temporally, the peak of the rainy season in Jember Regency occurs in December while the dry season is in August. In the rainy season (December-January and February) Jember Regency's rainfall is around 300-500 mm/month and in the dry season (June-July-August) it is in the range of 50-200 mm/month. Spatially, the northern part of Jember, especially Sumberbaru, Bangsalsari and Tanggul subdistricts, is wetter than the Jember Regency area as a whole. The southern part of Jember, especially those close to the coast, has lower rainfall than other regions. In the dry season, rainfall in this region is less than 20 mm/month.